Analytical prediction of cutting tool temperature distribution in orthogonal cutting including third deformation zone. (July 2021) - Barzegar, Zahra; Ozlu, Emre
Graphical abstract: Highlights: Third deformation zone should be included in the thermal analysis of machining. Cutting edge radius and clearance angle have critical impacts in temperature at flank face. Consideration of dual zone friction model yields to more realistic results. Increasing the cutting-edge radius six times, 50 % increase in the maximum flank temperature for AISI 1050 steel is observed. Increase of the clearance angle from 1° to 11°, results in 45 % decrease of maximum flank temperature for AISI1050 steel. Abstract: The present study introduces a novel model for the prediction of temperature in a cutting tool while the effects of all three deformation zones are considered. The model considers the effect of cutting-edge radius and the third deformation zone for the first time in the literature in terms of temperature prediction using thermo-mechanical approach with dual-zone friction model. The material behavior is defined by the Johnson-Cook constitutive model. For the calculation of heat flux on the rake and flank faces, a dual-zone model was used. The temperature distributions at the tool-chip and tool-workpiece boundaries were determined analytically, and the temperature distribution inside the tool was calculated using the Finite Difference Method. In order to verify the model, experiments were performed with AISI1050 steel and Al7075 workpiece materials using tungsten-carbide cutting tools. A good agreement is observed between the model predictions and the test results. This study also examined the effects of cutting-edge geometry and cutting conditions on cutting temperature, which can be used in optimized selection of cutting parameters and tool geometry.